How to train employees : a guide for managers - Williamson, Bobette Hayes (American Management Association, 2007)
Assess, design, deliver, and evaluate training that is right for every employee. As the global marketplace expands, the need for a flexible, well-trained workforce grows with it. Training employees to master business-critical skills has become a baseline requirement for managerial success. This book provides the tools and techniques to assess, design, deliver and evaluate training that is right for every employee. Based on a four-part training process, this book provides cases, exercises, worksheets and planning forms that make the learning immediate and dynamic and allow you to assemble the e.